Globalizing Māori Museology: Reconceptualizing Engagement, Knowledge, and Virtuality through Mana Taonga. (March 2016) - Schorch, Philipp; McCarthy, Conal; Hakiwai, Arapata
Abstract: This article sets out to globalize Māori museology through mana taonga, a concept that is historically grounded and articulated in contemporary museum practice. Mana taonga can be used to reconceptualize issues of engagement, knowledge, and virtuality by exploring ways in which the mutual, asymmetrical relations underpinning global, scientific entanglements of the past can be transformed into reciprocal, symmetrical forms of cross‐cultural curatorship and anthropology in the present. In doing so, the Cook/Forster Collection held at the Georg‐August‐Universität Göttingen, Germany, is being (re)approached from a Māori perspective. This collection embodies the first material evidence of the remarkable encounter between Pacific and European people in the 1700s and materializes the moment when two worlds of meaning became entangled and mutually constitutive with continuing significance for Pacific people and European understandings. Reconnecting both sides of the encounter through research on the history of the collection, its contemporary legacy, and Māori engagements with Western anthropology and museology allows us to correct lopsided (re)interpretations of indigenous cultures in exhibitionary projects and one‐sided accounts of museums and indigenous people that dominate the literature.